LGG-59. REMARKABLE OBJECTIVE RESPONSE AND FAVORABLE SURVIVAL FOR BRAF-V600E CHILDHOOD LOW-GRADE GLIOMAS TO BRAF INHIBITORS COMPARED CONVENTIONAL CHEMOTHERAPY - Zapotocky, Michal (Neuro Oncol, 2018)
Activation of the MAPK pathway represents a hallmark of pediatric low-grade glioma (pLGG) and is frequently caused by BRAF alterations. BRAF-V600E represent an aggressive type of pLGG with less than optimal response to conventional chemo-radiation approaches. While clinical trials using BRAF-V600E inhibitors are ongoing, these data are not yet available. We have assembled an international cohort of BRAF-V600E glioma patients treated off-label with BRAF inhibitors as a monotherapy. Complete molecular, clinical and imaging data is being collected and compared to previous chemo-radiation therapies. Ongoing data form the taskforce on 40 BRAF-V600E gliomas from 25 international institutions is summarized below. The most prevalent histologies were ganglioglioma, pilocytic astrocytoma and pleomorphic xanthoastrocytoma, located mainly in the chiasm, brainstem and temporal lobes. Strikingly, 66% of BRAF V600E pLGG patients achieved partial response (PR) to targeted inhibitors versus only 6.6% response to conventional chemotherapy (p<0.001). Five patients progressed during treatment 0.5 to 2.1 years after the start of BRAF inhibitor therapy. Additionally, 3 pLGG progressed after discontinuation of therapy. Two-year progression-free survival was 84.2% (95%CI,69.3-100) versus 50% (95%CI,32.2-77.5) with targeted agents and chemotherapy, respectively (p=0.021). Interestingly, 6 patients with BRAF V600E positive high-grade glioma did not exhibit objective responses to BRAF inhibitor therapy and the majority suffered from early progression. Our data suggest BRAF inhibitors to be potent therapeutic agents in BRAF-V600E pLGG but not HGG. Future studies aimed at mechanism of resistance and differential response to targeted agents are required.